Pseudomonas aeruginosa Homoserine Lactone Triggers Apoptosis and Bak/Bax-Independent Release of Mitochondrial Cytochrome C in Fibroblasts - Schwarzer, Christian (2014)
Pseudomonas aeruginosa use N-(3-oxododecanoyl)-homoserine lactone (C12) as a quorum-sensing molecule to regulate gene expression in the bacteria. It is expected that in patients with chronic infections with P. aeruginosa, especially as biofilms, local [C12] will be high and, since C12 is lipid soluble, diffuse from the airways into the epithelium and underlying fibroblasts, capillary endothelia and white blood cells. Previous work showed that C12 has multiple effects in human host cells, including activation of apoptosis. The present work tested the involvement of Bak and Bax in C12-triggered apoptosis in mouse embryo fibroblasts (MEF) by comparing MEF isolated from embryos of wild type (WT) and Bax(−/−)/Bak(−/−) (DKO) mice. In WT MEF C12 rapidly triggered (mins to 2 hr): activation of caspases 3/7 and 8, depolarization of mitochondrial membrane potential (Δφ(mito)) release of cytochrome C from mitochondria into the cytosol, blebbing of plasma membranes, shrinkage/condensation of cells and nuclei and, subsequently, cell killing. A DKO MEF line that was relatively unaffected by the Bak/Bax-dependent proapoptotic stimulants staurosporine and etoposide responded to C12 similarly to WT MEF: activation of caspase 3/7, depolarization of Δφ(mito) and release of cytochrome C and cell death. Re-expression of Bax or Bak in DKO MEF did not alter the WT-like responses to C12 in DKO MEF. These data showed that C12 triggers novel, rapid proapoptotic Bak/Bax-independent responses that include events commonly associated with activation of both the intrinsic pathway (depolarization of Δφ(mito) and release of cytochrome C from mitochondria into the cytosol) and the extrinsic pathway (activation of caspase 8). Unlike the proapoptotic agonists staurosporine and etoposide that release cytochrome C from mitochondria, C12’s effects do not require participation of either Bak or Bax.